Democracy and Democratization : Post-communist Europe in Comparative Perspective. - Nagle, John D. (SAGE Politics Texts Series., 1999)
This wide-ranging overview of the processes of democratization in post-Communist Europe, places the transitions in East-Central Europe within a broad European and global context. The authors begin with a introduction to the concept and theories of democracy and then examine the emerging politics of the new democracies to set the post-Communist transitions in longer-term comparative perspective with earlier and existing processes of democratization in. Southern Europe, Latin America, and East and Southeast Asia. Finally the politics of EU accession are introduced to place the transitions within.